Striving Towards ‘The Good Life’: What Environmental Litigation in India Can Tell Us About Climate Litigation in the Global South: Vedanta Ltd v. State of Tamil Nadu and Others , Supreme Court of India - Kumar, Parul (Transnational environmental law, 2024)
The Supreme Court of India's judgment in Vedanta Ltd v. State of Tamil Nadu and Others , affirming the closure of Vedanta's copper smelting plant in Tuticorin in southern India, concludes a long and contentious chain of litigation. The plant's troubled history and the ensuing litigation reflect contestations between economic development, environmental and social devastation, human well-being, and corporate responsibility, which are often characteristic of environmental litigation in the global south. This article analyzes the significance of the Indian Supreme Court's reliance on established constitutional rights principles as well as settled environmental jurisprudence, and highlights the relevance of this judicial pronouncement for climate litigation in the global south.